Endoscopic totally extraperitoneal repair for groin hernia: Experience from a tertiary care centre - Washim Firoz Khan; Yashwant Singh Rathore; Sandeep Aggarwal; Sunil Chumber; Prasanna Ramana Arumugaswamy; Khaja Abdul Moin Baig; Amit Patidar; Sanjeet Kumar Rai (Journal of Minimal Access Surgery, 2023)
Background: Totally extra-peritoneal (TEP) and transabdominal preperitoneal (TAPP) repair are two established minimal access techniques of groin hernia surgery. TEP offers the advantage of avoiding violation of the peritoneal cavity. Aim: This study aims to describe the decade-long experience of TEP in groin hernia repair in a tertiary care teaching institute and the feasibility of the same in difficult scenarios. Materials and Methods: Retrospective analysis of the database of patients undergoing TEP repair for inguinal hernia in a single surgical unit at a tertiary teaching hospital between January 2008 and December 2019 was performed. Detailed pre-operative clinical details, operative duration, intraoperative and post-operative complications, including pain, length of post-operative hospital stay and hernia recurrence data were analysed. Results: Over 12 years' duration, 511 patients underwent endoscopic TEP mesh repair and the total number of hernias repaired was 614. Majority (97.45%) of patients were male. The mean age of the patient population was 51.3 years. Primary hernia was seen in 490 patients. The mean operating time for unilateral inguinal hernia repair was 56.8 ± 16 min and for bilateral repair 80.9 ± 25.2 min. TEP in previous lower abdominal/suprapubic surgical scars was attempted in 17 (3.3%) patients, with only one requiring conversion. The intraoperative peritoneal breach was the most common documented complication (34.8%). Seroma was seen in 9.4% of patients. Seventeen patients required conversion (14 TAPP and 3 open). Recurrence was seen in 4 (0.7) patients. Conclusion: TEP repair is an effective method of groin hernia repair and can be attempted in the majority of patients groin hernia, including patients with previous lower abdominal incisions.